(untitled) (Communications in Computational Chemistry, 2018)
Based on density functional theory (DFT), the adsorption of atomic and molecular hydrogen and nitrogen on pyrite FeS_2 (100) surface was studied. Both atomic N and N_2 molecule prefer to adsorb on the top Fe site. The adsorption of atomic N on the surface of FeS_2 (100) is more stable than N_2. Adsorption energy calculation shows that the adsorption stability weakens with the increase of the N atom coverage. Hydrogen adsorption differs quite a lot with that of nitrogen adsorption. It is found that atomic H could stably adsorbs on FeS_2 (100) surface at the top Fe site, while H_2 molecule is quite difficult to adsorb on pyrite FeS_2 (100) surfaces. The adsorption stability of atomic hydrogen sharply weakens as the H coverage increases.